2016
DOI: 10.1073/pnas.1506552113
|View full text |Cite
|
Sign up to set email alerts
|

Covert digital manipulation of vocal emotion alter speakers’ emotional states in a congruent direction

Abstract: Research has shown that people often exert control over their emotions. By modulating expressions, reappraising feelings, and redirecting attention, they can regulate their emotional experience. These findings have contributed to a blurring of the traditional boundaries between cognitive and emotional processes, and it has been suggested that emotional signals are produced in a goaldirected way and monitored for errors like other intentional actions. However, this interesting possibility has never been experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 49 publications
3
64
1
Order By: Relevance
“…In order to change how a user perceives their voice, we used software that can manipulate a sound captured through a microphone and play back via headphone in less than 20 milliseconds [55]. Since the delay is minimum, the person attributes the sound that she hears through the headphone as her own voice [5]. With this approach, users should focus on their conversations without moving their attention away to the technology.…”
Section: Perceptionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to change how a user perceives their voice, we used software that can manipulate a sound captured through a microphone and play back via headphone in less than 20 milliseconds [55]. Since the delay is minimum, the person attributes the sound that she hears through the headphone as her own voice [5]. With this approach, users should focus on their conversations without moving their attention away to the technology.…”
Section: Perceptionmentioning
confidence: 99%
“…These values for voice modulation were used because in a previous study it was found that they lead to a perception of low arousal and calmness [5].…”
Section: Study 1: Conflicts Between Dating Couplesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study demonstrated that hearing one's own voice influences one's own mood, 15 suggesting that early deterioration of affective prosody could, therefore, negatively influence patients' mood. Fundamental frequency variation is known to be more useful for tracking within-patient changes than interindividual differences.…”
Section: Villain Et Al Affective Prosody and Depression After Stroke mentioning
confidence: 99%